2012
DOI: 10.1371/journal.pone.0043883
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Extensive Neurofilament Phosphorylation Rescues α-Internexin/Peripherin-Overexpressing PC12 Cells from Neuronal Cell Death

Abstract: Intermediate filament (IF) overproduction induces abnormal accumulation of neuronal IF, which is a pathological indicator of some neurodegenerative disorders. In our study, α-Internexin- and peripherin-overexpressing PC12 cells (pINT-EGFP and pEGFP-peripherin) were used as models to study neuropathological pathways responsible for neurodegenerative diseases. Microarray data revealed that Cdk5-related genes were downregulated and Cdk5 regulatory subunit-associated protein 3 (GSK-3α and GSK-3β) were upregulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Membranes were then probed with AlexaFluor® 488 goat α-rabbit IgG (1:250) or AlexaFluor® 488 goat α-mouse IgG 1 (1:250) for 1 h at 25 °C and visualized using a Typhoon 9410 Imager (GE Healthcare Life Sciences, Marlborough, MA). Membranes were also probed with mouse α-β-actin (1:5000; Novus Biologicals) [ 51 ] antibodies. All protein bands of interest were normalized to β-actin bands to act as a loading control.…”
Section: Methodsmentioning
confidence: 99%
“…Membranes were then probed with AlexaFluor® 488 goat α-rabbit IgG (1:250) or AlexaFluor® 488 goat α-mouse IgG 1 (1:250) for 1 h at 25 °C and visualized using a Typhoon 9410 Imager (GE Healthcare Life Sciences, Marlborough, MA). Membranes were also probed with mouse α-β-actin (1:5000; Novus Biologicals) [ 51 ] antibodies. All protein bands of interest were normalized to β-actin bands to act as a loading control.…”
Section: Methodsmentioning
confidence: 99%
“…The tails attain additional negative charges through serine phosphorylation which mediates the interaction between neighboring filaments, affects the organization of NF brushes and is considered to increase the lateral extension of sidearms [Martin et al, ]. Phosphorylation of NF‐H side arms also regulates transport of NFs through axons [Ackerley et al, ; Lee et al, ].…”
Section: Neurofilaments Are Specialmentioning
confidence: 99%
“…Together with other neuronal IF, peripherin constituted a shape‐maintaining IF network in mature neurons. It was reported that peripherin and α‐internexin can self‐assemble or co‐assemble with neurofilament protein subunits to form the filamentous structure before their translocation into the axons [Lee et al, ]. Neurofilament triplet proteins are constructed by the neurofilament light, medium and heavy subunits, all of which shared the same central rod domain with peripherin [Lee et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that peripherin and α‐internexin can self‐assemble or co‐assemble with neurofilament protein subunits to form the filamentous structure before their translocation into the axons [Lee et al, ]. Neurofilament triplet proteins are constructed by the neurofilament light, medium and heavy subunits, all of which shared the same central rod domain with peripherin [Lee et al, ]. Peripherin plays a crucial role in development of nervous system and it can be highly relevant to pathogenesis of neurodegenerative disorder.…”
Section: Discussionmentioning
confidence: 99%